Pulmonary embolism in children, a real challenge for the pediatrician: a case report and review of the literature - Maggio, Alessandra; Altieri, Lilia; Pantaleo, Dario; Grignani, Michela; Decembrino, Lidia (Acta Biomedica Atenei Parmensis, 2022)
Venous thromboembolism (VTE) is a coagulopathic disease that may appear with deep vein thrombosis (DVT), pulmonary embolism (PE), or both and is responsible for increased mortality and morbidity in children. We report a case of PE in a male teenager obese boy in the setting of a thrombophilic genetic disorder, infective condition, and immobility. Our experience underlines as PE in childhood is a multifactorial disease in which clinical risk factors and inherited thrombophilia contribute to the development. It is crucial to identify one or more risk factors leading to the most appropriate diagnostic workup.